A novel experimental approach for nanostructure analysis: simultaneous small-angle X-ray and neutron scattering - Metwalli, Ezzeldin; Götz, Klaus; Lages, Sebastian; Bär, Christian; Zech, Tobias; Noll, Dennis; Schuldes, Isabel; Schindler, Torben; Prihoda, Annemarie; Lang, Herbert; Grasser, Jürgen; Jacques, Mark; et al. (Journal of Applied Crystallography, 2020)
Exploiting small-angle X-ray and neutron scattering (SAXS/SANS) on the same sample volume at the same time provides complementary nanoscale structural information in two different contrast situations. Unlike an independent experimental approach, the truly combined SAXS/SANS experimental approach ensures the exactness of the probed samples, particularly for in situ studies. Here, an advanced portable SAXS system that is dimensionally suitable for installation in the D22 zone of ILL is introduced. The SAXS apparatus is based on a Rigaku switchable copper/molybdenum microfocus rotating-anode X-ray generator and a DECTRIS detector with a changeable sample-to-detector distance of up to 1.6 m in a vacuum chamber. A case study is presented to demonstrate the uniqueness of the newly established method. Temporal structural rearrangements of both the organic stabilizing agent and organically capped gold colloidal particles during gold nanoparticle growth are simultaneously probed, enabling the immediate acquisition of correlated structural information. The new nano-analytical method will open the way for real-time investigations of a wide range of innovative nanomaterials and will enable comprehensive in situ studies on biological systems. The potential development of a fully automated SAXS/SANS system with a common control environment and additional sample environments, permitting a continual and efficient operation of the system by ILL users, is also introduced.
CRIS-Team WoS Importer:2020-06-19

Atomic diffusion in liquid gallium and gallium-nickel alloys probed by quasielastic neutron scattering and molecular dynamic simulations - Shahzad, Anjum; Yang, Fan; Steffen, Julien; Neiß, Christian; Panchenko, Artem; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Embs, Jan Peter; Petry, Winfried; Lohstroh, Wiebke; Görling, Andreas; et al. (Journal of Physics: Condensed Matter, 2024)
The atomic mobility in liquid pure gallium and a gallium-nickel alloy with 2 at% of nickel is studied experimentally by incoherent quasielastic neutron scattering. The integral diffusion coefficients for all-atom diffusion are derived from the experimental data at different temperatures. DFT-based ab-initio molecular dynamics (MD) is used to find numerically the diffusion coefficient of liquid gallium at different temperatures, and numerical theory results well agree with the experimental findings at temperatures below 500 K. Machine learning force fields derived from ab-initio molecular dynamics (AIMD) overestimate within a small 6% error the diffusion coefficient of pure gallium within the genuine AIMD. However, they better agree with experiment for pure gallium and enable the numerical finding of the diffusion coefficient of nickel in the considered melted alloy along with the diffusion coefficient of gallium and integral diffusion coefficient, that agrees with the corresponding experimental values within the error bars. The temperature dependence of the gallium diffusion coefficient D Ga ( T ) follows the Arrhenius law experimentally for all studied temperatures and below 500 K also in the numerical simulations. However, D Ga ( T ) can be well described alternatively by an Einstein-Stokes dependence with the metallic liquid viscosity following the Arrhenius law, especially for the MD simulation results at all studied temperatures. Moreover, a novel variant of the excess entropy scaling theory rationalized our findings for gallium diffusion. Obtained values of the Arrhenius activation energies are profoundly different in the competing theoretical descriptions, which is explained by different temperature-dependent prefactors in the corresponding theories. The diffusion coefficient of gallium is significantly reduced (at the same temperature) in a melted alloy with natural nickel, even at a tiny 2 at% concentration of nickel, as compared with its pure gallium value. This highly surprising behavior contradicts the existing excess entropy scaling theories and opens a venue for further research.
CRIS-Team Scopus Importer:2024-02-16
Keywords: ab-initio molecular dynamics; DFT-based machine learning force fields; gallium-nickel alloy; liquid gallium; quasielastic neutron scattering; self-diffusion

Concentration dependent morphology and composition of n-alcohol modified cetyltrimethylammonium bromide micelles - Schmutzler, Tilo; Schindler, Torben; Götz, Klaus; Appavou, Marie-Sousai; Lindner, Peter; Prevost, Sylvain; Unruh, Tobias (Journal of Physics: Condensed Matter, 2018)
Cetyltrimethylammonitun bromide (CTAB) is one of the most commonly used surfactants in nanoparticle synthesis and stabilization. Usually, CTAB is used in high concentrations besides co-surfactants leading to well defined products but the complex mesoscopic CTAB structures stay mostly unknown. N-alcohols for instance are widely used co-surfactants which modify the properties of native CTAB dispersions. In this paper we report about a detailed structure analysis of n-alcohol modified CTAB micelles. In particular, n-pentanol and n-hexanol exhibit a significantly different influence on the size, shape and composition of CTAB micelles. Using a combination of small-angle x-ray spectroscopy (SAXS) and neutron scattering spectroscopy (SANS), we applied a method for a complete structural characterization of such micelles. The incorporation of n-pentanol into CTAB micelles generally does not influence the morphology but enhances the number of micelles due to the volume of the added alcohol. N-hexanol, however, leads to an elongation of the micelles as a function of its concentration. It was found by extended contrast variation measurements that this difference is caused by a different distribution of the alcohols between the micellar core and shell. N-pentanol molecules are generally located at the core-shell interface of the CTAB micelles with not only the head group but also two additional methylene bridging groups located in the micellar shell. This leads to an increase of its effective head group volume. In comparison, in n-hexanol modified micelles the whole alkyl chain is located within the micellar core. The detailed structure for n-alcohol modified CTAB micelles is described herein for the first time. The knowledge of the structural details found is indispensable for an in-depth understanding of CTAB-n-alcohol-water interfaces in general which is relevant for the synthesis of many functional nanostructures like mesoporous silica and gold or silver nanoparticles.
Keywords: CTAB; micelles; surfactants; co-surfactants; n-alcohols; SANS; SAXS

Effects of isotope and chemical incoherence on self-diffusion of atoms in liquid alloys of gallium with isotopes of nickel: Experiments based on quasielastic neutron scattering versus molecular dynamics simulations - Goychuk, Igor; Panchenko, Artem; Shahzad, Anjum; Fauser, Steffen; Neiß, Christian; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Hakim, Bishoy; Embs, Jan Peter; Englhard, Jonas; Bachmann, Julien; et al. (Physical Review B, 2025)
Quasielastic neutron scattering (QENS) is a powerful experimental technique to investigate the diffusion of atoms in liquids. It relies on the fact that at low 𝑄 values essentially only incoherent scattering is observed from the diffusing atoms. In the case of alloys composed of two chemical elements, it is commonly believed that at low 𝑄 QENS mainly probes the self-diffusion of the element with a nonzero incoherent scattering cross-section, while the element with a zero incoherent scattering cross-section does not contribute. However, the findings of this study challenge this belief. The study examines alloys of natural gallium (which has a nonzero incoherent scattering cross-section) and isotopes 58 Ni and 60 Ni (both of which have a zero incoherent scattering cross-section). A crucial factor to consider here is chemical incoherence, which typically leads to the renormalization of the incoherent cross-sections of different chemical elements within a mixture. Unfortunately, this renormalization is often disregarded in an ad hoc manner. Significantly, the alloy containing 58 Ni shows a notable renormalization, scattering incoherently to a similar degree as natural nickel in a comparable alloy with equivalent concentrations of chemical elements. Similarly perplexing, natural nickel scatters with great intensity despite being predominantly composed of 58 Ni and 60 Ni (around 94% of the total). This behavior can be attributed to the accepted phenomenon of isotope incoherence. We calculate the integral diffusion coefficients of Ga and Ni atoms in various liquid alloys from QENS experiments. These values are then compared to the results obtained from corresponding molecular dynamics simulations conducted at various temperatures, taking into account chemical incoherence. The comparison shows good agreement within the range of errors for the Ga1−𝑥⁢ 58Ni𝑥 alloy at two concentrations (𝑥=0.02 and 𝑥=0.1). The agreement also partially holds for the Ga1−𝑥⁢Ni𝑥 alloy with natural nickel and for the Ga1−𝑥⁢ 60Ni𝑥 alloy, despite certain difficulties discusse
CRIS-Team Scopus Importer:2025-02-17
Keywords: Diffusion; Alloys; Liquid metals; Ab initio molecular dynamics; Molecular dynamics; Neutron scattering

Epitaxial Metal Halide Perovskites by Inkjet-Printing on Various Substrates - Sytnyk, Mykhailo; Yousefi-Amin, Amir Abbas; Freund, Tim; Prihoda, Annemarie; Götz, Klaus; Unruh, Tobias; Harreiß, Christina; Will, Johannes; Spiecker, Erdmann; Levchuk, Jevgen; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2020)
Metal-halide-perovskites revolutionized the field of thin-film semiconductor technology, due to their favorable optoelectronic properties and facile solution processing. Further improvements of perovskite thin-film devices require structural coherence on the atomic scale. Such perfection is achieved by epitaxial growth, a method that is based on the use of high-end deposition chambers. Here epitaxial growth is enabled via a approximate to 1000 times cheaper device, a single nozzle inkjet printer. By printing, single-crystal micro- and nanostructure arrays and crystalline coherent thin films are obtained on selected substrates. The hetero-epitaxial structures of methylammonium PbBr(3)grown on lattice matching substrates exhibit similar luminescence as bulk single crystals, but the crystals phase transitions are shifted to lower temperatures, indicating a structural stabilization due to interfacial lattice anchoring by the substrates. Thus, the inkjet-printing of metal-halide perovskites provides improved material characteristics in a highly economical way, as a future cheap competitor to the high-end semiconductor growth technologies.
CRIS-Team Scopus Importer:2020-09-11
Keywords: epitaxial growth; inkjet printing; metal-halide-perovskites; single-crystal-microstructures

Highly Stable Lasing from Solution-Epitaxially Grown Formamidinium-Lead-Bromide Micro-Resonators - Afify, Hany A.; Sytnyk, Mykhailo; Rehm, Viktor; Barabash, Anastasia; Mashkov, Oleksandr; Osvet, Andres; Volobuev, Valentine V.; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Götz, Klaus; Unruh, Tobias; et al. (Advanced Optical Materials, 2022)
High-quality epitaxial growth of oriented microcrystallites on a semiconductor substrate is demonstrated here for formamidinium lead bromide perovskite, by drop casting of precursor solutions in air. The microcrystallites exhibit green photoluminescence at room temperature, as well as lasing with low thresholds. Lasing is observed even though the substrate is fully opaque at the lasing wavelengths, and even though it has a higher refractive index as the perovskite active material. Moreover, the lasing is stable for more than 109 excitation pulses, which is more than what is previously achieved for devices kept in the air. Such highly stable lasing under pulsed excitation represents an important step towards continuous mode operation or even electrical excitation in future perovskite-based devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: halide perovskites; lasing; microresonators; solution epitaxy

Hydrogenated anatase TiO2 single crystals: defects formation and structural changes as microscopic origin of co-catalyst free photocatalytic H2 evolution activity - Will, Johannes; Wierzbicka, Ewa; Wu, Mingjian; Götz, Klaus; Yokosawa, Tadahiro; Liu, Ning; Tesler, Alexander; Stiller, Markus; Unruh, Tobias; Altomare, Marco; Schmuki, Patrik; Spiecker, Erdmann (Journal of Materials Chemistry A, 2021)
Herein we systematically investigate the influence of hydrogenation time and temperature on defects formation, structural changes, and co-catalyst free photocatalytic activity for epitaxially grown anatase thin films on strontium titanate single crystals. The photocatalytic activity trend of the anatase epi layers is similar to that of anatase powders and brookite single crystals in reported recent literature, that is, the H2 evolution rate exhibits a typical maximum upon hydrogenation under moderate annealing temperatures (500 °C). By combining surface sensitive X-ray diffraction methods and analytical high-resolution electron microscopy techniques we reveal quantitatively the oxygen loss from the epi-layer ascribed to the hydrogenation (H2 reduction) treatment. We observe specific physicochemical changes associated with the introduction of oxygen vacancies: (i) the formation of a nanoscale strained crystal surface, (ii) the agglomeration of point defects in the bulk of the anatase epi layer, and (iii) a transition towards a Ti2O3 like symmetry at the film surface, i.e. an evident oxygen deficiency at the epi layer surface in particular prominent for the most active sample as a function of the hydrogenation parameters. These extensive experimental findings allow us to propose an empirical model, which links detrimental and beneficial effects of Ti3+ centers and oxygen vacancies in the bulk and at the surface and their abundance to an optimum point defect configuration for water splitting via “grey” anatase.

Internal Structure of Nanometer-Sized Droplets Prepared by Antisolvent Precipitation - Schuldes, Isabel; Noll, Dennis; Schindler, Torben; Zech, Tobias; Götz, Klaus; Appavou, Marie Sousai; Boesecke, Peter; Steiniger, Frank; Schulz, Peter; Unruh, Tobias (Langmuir, 2019)
Antisolvent precipitation (AP) is a low-cost and less-invasive preparation alternative for organic nanoparticles compared to top-down methods such as high-pressure homogenization or milling. Here we report on particularly small organic nanoparticles (NPs) prepared by AP. It has been found for various materials that these NPs in their liquid state exhibit a significant degree of molecular order at their interface toward the dispersion medium including ubiquinones (coenzyme Q10), triglycerides (trimyristin, tripalmitin), and alkanes (tetracosane). This finding is independent of the use of a stabilizer in the formulation. While this is obviously a quite general interfacial structuring effect, the respective structural details of specific NPs systems might differ. Here, a detailed structural characterization of very small liquid coenzyme Q10 (Q10) NPs is presented as a particular example for this phenomenon. The Q10 NPs have been prepared by AP in the presence of two different stabilizers, sodium dodecyl sulfate (SDS) and pentaethylene glycol monododecyl ether (C12E5), respectively, and without any stabilizer. The NPs' size is initially analyzed by photon correlation spectroscopy (PCS). The SDS-stabilized Q10 NPs have been studied further by differential scanning calorimetry (DSC), small-angle X-ray and neutron scattering (SAXS, SANS), wide-angle X-ray scattering (WAXS), and cryogenic transmission electron microscopy (CryoTEM). A simultaneous analysis of SAXS and contrast variation SANS studies revealed the molecular arrangement within the interface between the NPs and the dispersion medium. The Q10 NPs stabilized by SDS and C12E5, respectively, are small (down to 19.9 nm) and stable (for at least 16 months) even when no stabilizer is used. The SDS-stabilized Q10 NPs reported here, are therewith, to the best of our knowledge, the smallest organic NPs which have been reported to be prepared by AP so far. In particular, these NPs exhibit a core-shell structure consisting of an amorphous Q10 core and a surrounding shell, which is mainly composed of oriented Q10 molecules and aligned SDS molecules. This structure suggests a significant amphiphilic behavior and a rather unexpected stabilizing role of Q10 molecules.
CRIS-Team Scopus Importer:2019-10-22

Investigating Growth of Gold Nanorods by Simultaneous Small-Angle X-Ray and Neutron Scattering - Zech, Tobias; Metwalli, Ezzeldin; Götz, Klaus; Schuldes, Isabel; Porcar, Lionel; Unruh, Tobias (Particle & Particle Systems Characterization, 2022)
Increased usage of gold nanorods (AuNRs) in various biosensing and medical applications requires tight size and morphology control. This is often achieved by tuning the aggregation behavior of the stabilizing ligand cetrimonium bromide (CTAB). Because the role of CTAB during AuNR growth is still a matter of debate, simultaneous small-angle X-ray and neutron scattering experiments (SAXS/SANS) and measurements are performed. The SAXS/SANS measurements have enabled an instantaneous correlation between the size of evolving AuNR and the nanostructure of guiding CTAB moieties. Upon modifying the aggregation behavior of CTAB micelles by adding hexanol or pentanol as inert additives in the precursor solution, a marked change in reaction kinetics is observed. Alcohol-modified CTAB nanostructures have improved AuNR size uniformity compared to those prepared in alcohol-free CTAB solutions, which are attributed to different growth modes. The change in reaction kinetics is linked to a changed stabilization mechanism of reactants and nascent AuNR facilitated by CTAB micelles.
CRIS-Team WoS Importer:2022-02-18

Mesoscopic Structure of Lipid Nanoparticle Formulations for mRNA Drug Delivery: Comirnaty and Drug-Free Dispersions - Unruh, Tobias; Götz, Klaus; Vogel, Carola; Fröhlich, Erik; Scheurer, Andreas; Porcar, Lionel; Steiniger, Frank (ACS nano, 2024)
Lipid nanoparticles (LNPs) produced by antisolvent precipitation (ASP) are used in formulations for mRNA drug delivery. The mesoscopic structure of such complex multicomponent and polydisperse nanoparticulate systems is most relevant for their drug delivery properties, medical efficiency, shelf life, and possible side effects. However, the knowledge on the structural details of such formulations is very limited. Essentially no such information is publicly available for pharmaceutical dispersions approved by numerous medicine agencies for the use in humans and loaded with mRNA encoding a mimic of the spike protein of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) as, e.g., the Comirnaty formulation (BioNTech/Pfizer). Here, we present a simple preparation method to mimic the Comirnaty drug-free LNPs including a comparison of their structural properties with those of Comirnaty. Strong evidence for the liquid state of the LNPs in both systems is found in contrast to the designation of the LNPs as solid lipid nanoparticles by BioNTech. An exceptionally detailed and reliable structural model for the LNPs i.a. revealing their unexpected narrow size distribution will be presented based on a combined small-angle X-ray scattering and photon correlation spectroscopy (SAXS/PCS) evaluation method. The results from this experimental approach are supported by light microscopy, 1H NMR spectroscopy, Raman spectroscopy, cryogenic electron microscopy (cryoTEM), and simultaneous SAXS/SANS studies. The presented results do not provide direct insights on particle formation or dispersion stability but should contribute significantly to better understanding the LNP drug delivery process, enhancing their medical benefit, and reducing side effects.
CRIS-Team Scopus Importer:2024-04-12
Keywords: BNT162b2 Comirnaty; dynamic light scattering (DLS; lipid nanoparticles (LNPs); mRNA drug delivery; PCS); proton nuclear magnetic resonance spectroscopy (; severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2); small-angle X-ray scattering (SAXS)

Multifunctional and Tunable Surfaces Based on Pyrene Functionalized Nanoparticles - Wittmann, Judith; Stiegler, Lisa; Henkel, Christian; Träg, Johannes; Götz, Klaus; Unruh, Tobias; Zahn, Dirk; Hirsch, Andreas; Guldi, Dirk Michael; Halik, Marcus (Advanced Materials Interfaces, 2019)
The tuning of the optical properties of pyrene, immobilized on alumina nanoparticle surfaces, is demonstrated. To this end, phosphonic acid functionalized pyrene derivatives are shown to self‐assemble into stoichiometrically mixed monolayers featuring hydrophilic, hydrophobic, or fluorophilic phosphonic acid ligands and to form defined core–shell hybrids depending on the molecular mixing ratio and the nature of the ligand monomer, excimer, or mutual emission of both evolved. The spectroscopic observations are explained by the respective mobility of the dye molecules with respect to their fixed, specific anchor points and the resulting probability to form excimers and are supported by molecular dynamic simulations, X‐ray reflectivity measurements, and temperature‐dependent steady‐state fluorescence assays. In terms of an additional tuning of the emission color change and/or the on‐off switching of the fluorescence, the formation of core–shell–shell system is carried out by applying amphiphiles. The general concept is fully transferable to demobilized films of nanoparticles, thereby enabling a switchable solid‐state surfac

Nucleation Behavior of SnS2 on Thiol Functionalized SAMs During Solution-Based Atomic Layer Deposition - Götz, Klaus; Prihoda, Annemarie; Shen, Chen; Dierner, Martin; Dallmann, Johannes; Prusch, Saskia; Zahn, Dirk; Spiecker, Erdmann; Unruh, Tobias (Advanced Materials Interfaces, 2024)
Solution-based atomic layer deposition (sALD) is an emerging technique that transfers the principle of traditional atomic layer deposition (ALD) from the gas phase into a wet chemical environment. This new preparation technique has new and unique properties and requirements. A large number of new surfaces and reactants are available to produce active 2D materials. In this work a reproducible procedure to coat silicon wafers with a densely packed monolayer of (3-Mercaptopropyl)trimethoxysilane (MPTMS) molecules is presented. These highly functionalized surfaces can be used to seed the nucleation of SnS2 in a solution-based ALD procedure. A coating routine for the production of SnS2 is adapted from ALD to sALD and insight into the nucleation behavior of the reactands is given. X-ray reflectometry (XRR) is used to resolve the nucleation process of SnS2 on an MPTMS self assembled monolayer (SAM) during the first three cycles of an sALD procedure. The comparison of ex situ XRR, in situ XRR, grazing incidence wide-angle X-ray scattering (GIWAXS), atomic force microscopy (AFM), energy dispersive X-ray spectroscopy (EDX) measurements, and density functional theory (DFT) calculations find that SnS2 first forms a closed layer and then continues to grow in islands on thiol functionalized silane SAMs. Subsequent coating cycles will continue the growth of the islands laterally and in height.
CRIS-Team Scopus Importer:2024-08-09
Keywords: AFM; GIWAXS; sALD; SAM; solution atomic layer deposition; XRR

Porphyrin adsorption and ligand exchange at the (110)-TiO2 / organic liquid interface - Götz, Klaus; Stollberg, Isabella; Prihoda, Annemarie; Bertram, Florian; Metwalli, Ezzeldin; Zech, Tobias; Unruh, Tobias (Surface Science, 2022)
Highly efficient dye-sensitized solar cells (DSSCs) have been prepared on the basis of porphyrin dyes with significant success. Recent studies have demonstrated a correlation between the solar cell efficiency and the configuration of the adsorbed porphyrin molecules at the surface of the semiconducting support material. The preparation of dense self assembled monolayers (SAMs) of upright standing porphyrin molecules on TiO2 surfaces was achieved from toluene solutions only when using a molecular exchange reaction. Here, an exchange study of an oleic acid (OLA) SAM on a <110> TiO2 surface by porphyrin molecules is presented. The exchange reaction has been studied by ex-situ as well as in-situ X-ray reflectometry (XRR) measurements. It was found that an almost complete exchange of OLA with porphyrins can be achieved. With increasing coating times the orientation of the porphyrin molecules relative to the substrate surface changed from flat lying to upright standing.
CRIS-Team Scopus Importer:2022-04-15
Keywords: DESY; functionalization; interface; porphyrin; rutile; X-ray reflectometry

Simultaneous SAXS/SANS Method at D22 of ILL: Instrument Upgrade - Metwalli, Ezzeldin; Götz, Klaus; Zech, Tobias; Bär, Christian; Schuldes, Isabel; Martel, Anne; Porcar, Lionel; Unruh, Tobias (Applied Sciences, 2021)
A customized portable SAXS instrument has recently been constructed, installed, and tested at the D22 SANS instrument at ILL. Technical characteristics of this newly established plug-and-play SAXS system have recently been reported (J. Appl. Cryst. 2020, 53, 722). An optimized lead shielding arrangement on the SAXS system and a double energy threshold X-ray detector have been further implemented to substantially suppress the unavoidable high-energy gamma radiation background on the X-ray detector. The performance of the upgraded SAXS instrument has been examined systematically by determining background suppression factors (SFs) at various experimental conditions, including different neutron beam collimation lengths and X-ray sample-to-detector distances (SDDX-ray). Improved signal-to-noise ratio SAXS data enables combined SAXS and SANS measurements for all possible experimental conditions at the D22 instrument. Both SAXS and SANS data from the same sample volume can be fitted simultaneously using a common structural model, allowing unambiguous interpretation of the scattering data. Importantly, advanced in situ/real time investigations are possible, where both the SAXS and the SANS data can reveal time-resolved complementary nanoscale structural information.<br
CRIS-Team Scopus Importer:2021-07-16
Keywords: Nanomaterials; SANS; SAS; SAXS; Small angle neutron scattering; Small angle X-ray scattering

Solution-Growth Liquid-Phase Epitaxy of CsPbBr3 on NaCl by Optimizing the Substrate Dissolution - Elia, Jack; Levchuk, Ievgen; Hou, Yi; Matt, Gebhard; These, Albert; Zhao, Yicheng; Zhang, Jiyun; Forberich, Karen; Osvet, Andres; Götz, Klaus; Prihoda, Annemarie; Wu, Mingjian; et al. (Journal of Physical Chemistry C, 2023)
Since the earliest days of liquid-phase epitaxy (LPE) research, substrate stability has been a prerequisite for investigating nucleation and epitaxial growth. For flux- and melt-growth LPE, soluble substrates have always been viewed as problematic and difficult. However, solution-growth LPE transforms this disadvantage into a benefit by facilitating the creation of graded interfaces. In this study, we investigated the nucleation and growth of solution-grown LPE in the evaporation mode of soluble CsPbBr3 on freshly cleaved NaCl single-crystal substrates. Only two of the four main types of CsPbBr3 crystallization observed are epitaxial. The microscopic observation of composition gradients at the interface of CsPbBr3 grains and substrates reveals a promising opportunity to manipulate the lattice constant at the interface by simply controlling the temperature and concentration.
CRIS-Team Scopus Importer:2023-12-08

Squeezing the Threshold of Metal-Halide Perovskite Micro-Crystal Lasers Grown by Solution Epitaxy - Zhou, Shuyu; Rehm, Viktor; Afify, Hany A.; Feng, Yufei; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Peng, Zijian; These, Albert; Barabash, Anastasia; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2024)
Metal halide perovskite semiconductors have demonstrated remarkable progress not only in photovoltaics and X-ray detection but also in laser technologies. Particularly appealing is the simplicity with which micro-crystallites can be epitaxially grown, thereby forming micro-resonators suitable for lasing. Here, the laser threshold is optimized by selecting excitation laser parameters and by improving material quality. The latter process is conducted for formamidinium lead tribromide, emitting in the green spectral range. Depending on the growth method and parameters, the sizes of the micro-resonators can be tuned between ≈3 and 23 micrometers. Under laser excitation systematically lower thresholds are observed for micro-resonators in the 4–7 micrometer size range, than for larger ones, irrespective of growth method. Among three optimized growth methods, epitaxial growth via antisolvent vapor-assisted crystallization exhibits the smallest threshold powers, indicating the highest material quality. This conclusion is supported by hyperspectral microscopic luminescence imaging and by transient photoluminescence. The best laser structures exhibit record threshold powers for epitaxially grown perovskites, indicating that the selected antisolvent vapor epitaxial growth holds great promises also for other perovskite materials.
CRIS-Team Scopus Importer:2024-05-10
Keywords: FAPbBr; lasing; micro-resonators; perovskites; solution epitaxy

Systematic approach to measure the performance of microchannel-plate photomultipliers - Lehmann, Albert; Böhm, Merlin; Götz, Klaus; Gumbert, Katja; Krauss, Steffen; Miehling, Daniel; Pfaffinger, Markus (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2024)
In this paper, we present our approach to systematically measure numerous performance parameters of microchannel plate photomultiplier tubes. The experimental setups, the analyses and selected results are discussed. Although the techniques used may be different in other locations, the document is intended as a guide for comparable measurements with other types of microchannel plate photomultiplier tubes. Measurements are shown for the following performance parameters: spectral and spatial quantum efficiency, collection efficiency, gain as a function of voltage, position and magnetic field, time resolution, rate capability and lifetime. By using a dedicated 3-axis stepper and an FPGA-based data acquisition system, also inner PMT parameters are measured as a function of the active area, such as relative detection efficiency, dark count rate, time resolution, recoil electron and afterpulse distributions, as well as charge sharing and electronic crosstalk. In addition, some of the parameters are investigated inside a strong magnetic field. For many of these measurements, the change of most setup parameters and the subsequent analysis can be controlled semi-automatically by software scripts.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Afterpulses; Collection efficiency; Crosstalk; Dark count rate; Gain; Lifetime; Magnetic field; Multianode microchannel-plate PMTs; PANDA; Performance parameters; Quantum efficiency; Rate capability; Recoil electrons; Time resolution

The evolution of crystalline ordering for ligand-ornamented zinc oxide nanoparticles - Zobel, Mirijam; Windmueller, Anna; Schmidt, Ella; Götz, Klaus; Milek, Theodor; Zahn, Dirk; Kimber, Simon A. J.; Hudspeth, Jessica M.; Neder, Reinhard (Crystengcomm, 2016)
Recent total scattering experiments have opened up the possibility to study nanoparticle formation in situ and to observe the structural transformation from precursor clusters to adult particles. Organic ligand molecules interact with precursors of metal oxide nanoparticles, yet their influence onto the evolution of crystallinity during particle formation has not been addressed in detail; nor have in situ total scattering experiments ventured into the field of low-concentration, room-temperature syntheses in organic solvents to date. In this report, we follow the crystallization of ZnO nanoparticles in ethanol in the presence of different organic ligands. Low coordinated zinc precursor clusters rapidly polymerize upon base addition to particles of ca. 1 nm in diameter. In situ SAXS experiments reveal that the overall particle size increases to 2 to 4 nm with advancing reaction time. Complementary in situ PDF experiments show smaller crystalline domain sizes, which are only one third to half as large as the particle diameter. The ZnO particles thus feature a crystalline core surrounded by a disordered shell. Both, the core and the shell diameter are influenced by the different surface-bound organic ligands, which prevent an immediate relaxation to fully crystalline particles. A slow crystallization takes place in solution. We assume a dynamic equilibrium of the ligand and solvent molecules at the particle surface, which enables gradual bond restructuring. With suitably adjusted synthesis conditions, in our case by a continuous base addition, we show how to bypass the disordered intermediates, allowing the spontaneous nucleation of fully crystalline nanoparticles.

Unraveling Complexity: A Strategy for the Characterization of Anisotropic Core Multishell Nanoparticles - Lin, Wei; Greve, Christoph; Härtner, Sebastian; Götz, Klaus; Walter, Johannes; Wu, Mingjian; Rechberger, Stefanie; Spiecker, Erdmann; Busch, Sebastian; Schmutzler, Tilo; Avadhut, Yamini; Hartmann, Martin; et al. (Particle & Particle Systems Characterization, 2020)
In this work, a widely applicable routine to characterize the core, surface, stability, and optical properties of CdSe/CdS/ZnS core–shell–shell nanorods after multiple growth steps is established. First, size, shape, and shell thickness of the nanorods are characterized by transmission electron microscopy (TEM), analytical ultracentrifugation (AUC), and small angle X-ray/neutron scattering (SAXS/SANS). In the next step, Fourier-transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), and SANS measurements are applied to determine the surface species of nanorods. Then, the colloidal stability of the nanorods is investigated by UV–vis spectroscopy and dynamic light scattering (DLS) after different washing cycles. Finally, photoluminescence quantum yield (PLQY) of the nanorods during washing and sample storage is determined. With this highly complementary routine for particle characterization, the core, surface, stability, and optical properties of nanorods after multiple growth steps are resolved. The results demonstrate the importance of the developed toolbox to characterize such highly complex, anisotropic nanorods for a technical environment. This is of major importance for the handling of colloidal quantum materials and their quality control in industrial applications.
CRIS-Team Scopus Importer:2020-09-11
Keywords: anisotropic; characterization; core multishell; nanoparticles